2009
DOI: 10.1007/s00134-009-1637-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and monocyte CD64 indexes, lipopolysaccharide-binding protein, procalcitonin and C-reactive protein in sepsis of critically ill neonates and children

Abstract: Neutrophil CD64 index (CD64in) is the best individual marker for bacterial sepsis in children, while in neonates the highest diagnostic accuracy at the time of suspected sepsis was achieved by LBP and 24 h later by CD64in.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 39 publications
3
81
1
Order By: Relevance
“…Impact of septic etiology on levels of bacterial inflammation markers ought not to be negated as well. In the aforementioned study, gram-positive flora prevailed in all the cases of confirmed sepsis [17]. In our group of patients, both gram-positive and gram-negative causative agents were observed in the positive hemoculture.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Impact of septic etiology on levels of bacterial inflammation markers ought not to be negated as well. In the aforementioned study, gram-positive flora prevailed in all the cases of confirmed sepsis [17]. In our group of patients, both gram-positive and gram-negative causative agents were observed in the positive hemoculture.…”
Section: Resultssupporting
confidence: 56%
“…In this study, white blood CD64 index reflecting the CD64 expression level on neutrophil membrane was compared to procalcitonin and C-reactive protein -indicators that are frequently used in cardiac surgical practice. The analysis revealed that the CD64 index is a good early marker of sepsis with high sensitivity (80%) and specificity (90%), AUC -0.895 (0.753-1.000) and cutoff point 2.00; this corresponds to the results of other studies of neonates and infants at multi-profile children's units [17,18]. For instance, in a study carried out on patients at the multi-profile pediatric intensive care unit, the highly informative values of the CD64 index were 2.38 or higher for infants (aging from 28 days to 12 months) and 1.86 or higher for neonates (respective AUC values amounted to 0.88 and 0.82, sensitivity values -to 71 and 77%, specificity values -to 100 and 79%, positive prognostic value -100 and 53%, negative prognostic value -96 and 92%) [17].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…A smal ler study in cri ti cal ly ill neo na tes and in fan ts by Gro se ljGre nc used the stan dar di zed CD64 in dex for the fi r st ti me and de mon stra ted its su pe rio ri ty over all ot her in fec tion mar ke rs (29). In a fol low-up stu dy the sa me aut ho rs pre sen ted evi den ce that neutrop hil CD64 was the be st in di vi dual mar ker for bac te rial sep sis in chil dren, whe reas the te st perfor med so mewhat le ss in neo na tes (32). Howe ver, bo th pa tie nt grou ps we re of li mi ted si ze and might ac tual ly not war ra nt this con clu sion.…”
Section: Tab Lementioning
confidence: 99%